TREE SPECIES COMPOSITION AND DIVERSITY IN DANSOSHIYA FOREST RESERVE, KANO STATE, NIGERIA - Yusuf, Mohammed Sunusi (FUDMA JOURNAL OF SCIENCES, 2025)
It is essential to document the composition and diversity of tree species, particularly in light of an urgent need for biodiversity conservation, ecosystem management, and the requirements by key tree species conservation players. This study was carried out to assess the composition and diversity of tree species in the Dansoshiya Forest Reserve (DFR). The study conducted a detailed fieldwork, 30 stratified random sample plots with a quadrat size of 12.5m x 8m were collected and measured across the five strata of the study area. Botanical exploration and analytical results successfully identified a total of 67 tree species, distributed among 24 families and 55 genera, with a total count of 1,554 individual tree stands. The Fabaceae family, comprising 32.8% of the total, while families such as Anacardiaceae, Annonaceae, Bignoniaceae, Burseraceae, Dioscoreaceae, Ebenaceae, Lamiaceae, Loganiaceae, Olacaceae, Polygalaceae, Sapotaceae, and Zygophyllaceae were the least represented, each accounting for only 1.5% of species. Species diversity analysis showed that Combretum molle was the most abundant, ranked first, while Cassia singueana, Ceiba pentandra, Ficus platyphylla, Piliostigma thonningii, and Securinega virosa had the fewest individuals, all ranked 30. The results indicated that, although the area is rich in species diversity, certain families are poorly represented, hence the need for regular assessment to prevent the potential loss of tree species in DFR.
Keywords: Biodiversity; Conservation; Species composition; Species diversity; Dansoshiya